Investigation on wear resistance and corrosion resistance of electron beam cladding co-alloy coating on Inconel617. (11th April 2018) - Liu, Hailang; Zhang, Guopei; Huang, Yiping; Qi, Zhengwei; Wang, Bo; Yu, Zhibiao; Wang, Dezhi
Abstract: To improve surface properties of Inconel 617 alloy (referred to as 617 alloy), co-alloy coating metallurgically bonded to substrate was prepared on the surface of 617 alloy by electron beam cladding. The microstructure, phase composition, microhardness, tribological properties and corrosion resistance of the coatings were investigated. The XRD results of the coatings reinforced by co-alloy (Co800) revealed the presence of γ -Co, CoC x and Cr23 C6 phase as matrix and new metastable phases of Cr2 Ni3 and Co3 Mo2 Si. These hypoeutectic structures contain primary dendrites and interdendritic eutectics. The metallurgical bonding forms well between the cladding layer and the matrix of 617 alloy. In most studied conditions, the co-alloy coating displays a better hardness, tribological performance, i.e., lower coefficient of frictions and wear rates, corrosion resistance in 1 mol L −1 HCl solution, than the 617 alloy.